Energy transfer, anticounterfeiting, white light emission and sensing in fine-regulating series of lanthanide metal-organic frameworks - Xue, Juanjuan; Wang, Yao; Yang, Guoping; Wang, Yaoyu (Journal of rare earths, 2024)
Three lanthanide ions and a rigid (1,1'-biphenyl)-2,4,6-tricarboxylic acid (H3bptc) ligand led to the isostructural lanthanide metal-organic frameworks (Ln-MOFs) {[Ln(bptc) (H2O)3]·3H2O}n (Lnbptc, Ln = Eu, Tb, Gd, EuxTb1–x, EuxGd1–x, TbxGd1–x, and Eu0.12Tb0.52Gd0.36). The density functional theory (DFT) and time-dependent DFT calculation were expanded on H3bptc, which point to the occurrence of “antenna effect”. The minor diameter samples of Eubptc, Tbbptc, and Gdbptc can also be attained via the microwave synthesis and employed for handwriting anticounterfeiting. Interestingly, the typical red emission of Eu3+ and green emission of Tb3+ could be fine-tuned by Gd3+ via chemical mixing to be full-color emissions bimetallic doped EuxTb1–xbptc, EuxGd1–xbptc, and TbxGd1–xbptc. The above synthetic bimetallic MOFs can be fixed in positioning boxes of quick response (QR) codes with diverse emission for anticounterfeiting. The message can be decoded under the irradiation of 365 nm ultraviolet lamp while invisible in the daylight. Notably, the trimetallic doped Eu0.12Tb0.52Gd0.36bptc emits white light with the CIE color coordinate (0.34, 0.34). Furthermore, Tbbptc is demonstrated to be a sensitive probe toward nitrobenzene and acetone with multiple mechanisms. Three lanthanide metal ions and a rigid (1,1'-biphenyl)-2,4,6-tricarboxylic acid (H3bptc) ligand led to isostructural lanthanide metal-organic frameworks {[Ln(bptc)(H2O)3]·3H2O}n (Lnbptc, Ln = Eu, Tb, Gd, EuxTb1–x, EuxGd1–x, TbxGd1–x and Eu0.12Tb0.52Gd0.36). Based on their excellent luminescence, the related performances were studied carefully, such as handwriting anticounterfeiting, quick response codes anticounterfeiting, white light emission and sensing properties. [Display omitted] •The minor diameter samples of Lnbptc (Ln = Eu, Tb, and Gd) were attained via microwave synthesis and employed for handwriting anticounterfeiting.•The typical red emission of Eu3+ and green emission of Tb3+ could be fine-tuned by Gd3+via chemical mixing to be full-color emissions bimetallic doped materials.•The synthetic bimetallic MOFs could be fixed in positioning boxes of quick response (QR) codes with diverse emissions for anticounterfeiting.•The trimetallic doped Eu0.12Tb0.52Gd0.36bptc emits white light with the CIE color coordinate (0.34, 0.34).•Furthermore, Tbbptc was demonstrated a sensitive probe toward nitrobenzene and acetone with multiple mechanisms.